Local therapy treatment conditions for oligometastatic non-small cell lung cancer - Zhang, Suli; Sun, Qian; Cai, Feng; Li, Hui; Zhou, Yufu (Frontiers in Oncology, 2022)
Standard treatments for patients with metastatic non-small cell lung cancer (NSCLC) include palliative chemotherapy and radiotherapy, but with limited survival rates. With the development of improved immunotherapy and targeted therapy, NSCLC prognoses have significantly improved. In recent years, the concept of oligometastatic disease has been developed, with randomized trial data showing survival benefits from local ablation therapy (LAT) in patients with oligometastatic NSCLC (OM-NSCLC). LAT includes surgery, stereotactic ablation body radiation therapy, or thermal ablation, and is becoming an important treatment component for OM-NSCLC. However, controversy remains on specific management strategies for the condition. In this review, we gathered current randomized trial data to analyze prognostic factors affecting patient survival, and explored ideal treatment conditions for patients with OM-NSCLC with respect to long-term survival.